Real time ECG signal monitoring using IoT gateway - Hema, L. K.; Vanitha, V.; Vijay, J.; Kumar Dwibedi, Rajat (International Journal of Psychosocial Rehabilitation, 2020)
-Electrocardiogram is a health taping apparatus which is used to track Human heart electrical activity. Each heart beat is triggered by the phases of this electrical activity of excitation (depolarisation) and recovery (polarization). This patient history of the ECG is very important to detect or diagnose heart disease viz., regurgitation of the aortic valve, coronary artery disease, mitral stenosis etc. In our work we proposes to establish an ECG tracking system linked to the Internet of Things and simultaneously store data to the cloud at very inexpensive prices. The medical and paramedic health professionals (Android device) are able to track the patient's heart activity on a continuous basis and can fully remove the assistance near the patient. The medical and med tech medical practitioners (Android device) are capable of controlling the sufferer's cardiac output on an ongoing basis and can remove the aid around the person completely. A three lead sensor module called with electrode leads ADS1292R allows the patient to be positioned above the thorax.